SOSIALISASI PENTINGNYA CRITICAL THINKING UNTUK MEMBANGUN GENERASI MUDA YANG KRITIS DALAM KEGIATAN LATIHAN DASAR KEPEMIMPINAN SISWA SMA CITRA ISLAMI CIKUPA - Isnaini Mahuda; Miftahul Huda (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
Critical thinking is one of the abilities that every individual must possess in order to be able to adapt to increasingly complex life. This critical thinking ability is also crucial for every leader to support the proper analysis and decision making. As the young generation of future leaders, students need this critical thinking ability. Therefore, socialization was carried out regarding the importance of critical thinking to build a critical young generation. This Community Service Activity is a series of Student Leadership Basic Training activities at SMA Citra Islami Cikupa. The socialization process was carried out by giving lectures and discussions with the activity participants and an evaluation using a questionnaire. The results of this Community Service activity provide conclusions including 1) socialization about the importance of critical thinking skills or critical thinking goes well and is followed with great enthusiasm by prospective student council administrators; 2) this socialization is also a provision for prospective student council administrators as the young generation of future leaders to continue to hone their critical skills